STUDI TENTANG PESERTA DIDIK YANG KECANDUAN PORNOGRAFI DI SEKOLAH MENENGAH KEJURUAN NEGERI 7 PONTIANAK - Imaroh, Lailatul; Yuline, Yuline; Fergina, Ana (Universitas Tanjungpura, 2024)
This research aims to find out how students who are addicted to pornography. Using a descriptive qualitative approach. The data source of this research is two students of class X SMK Negeri 7 Pontianak who are determined through a questionnaire. The method used is descriptive method with direct communication data collection techniques. Data analysis uses an interactive model consisting of data reduction, data presentation and conclusion drawing stages. The results showed that the characteristics of pornography addiction are anti-social, forgetting time, often talking dirty, declining academic grades, wasting money, and often masturbating. Internal factors of pornography addiction are curiosity, curiosity and lack of activities to fill empty time. External factors are being influenced by friends, being influenced by the internet and social media, lack of love and role models. The impact of pornography addiction is difficult to control lust, often lying, fantasizing dirty things. The role of parents in helping students who are addicted to pornography has not been implemented. The role of Guidance and Counseling teachers for students who are addicted to pornography has not been implemented. Thus it can be concluded that students who are addicted to pornography have distinctive signs, causes both from internal and external factors, and has a negative impact on students.